Mycological Characterization Of White Pustule Symptom On Ipomea Reptans Poir Leaves In Bogor-Indonesia - Putra, Ivan Permana; Amelya, Mega Putri (Biosel Biology Science and Education, 2020)
Ipomoea reptans Poir. (Convolvulaceae) is one of the favorite vegetables consumed by Indonesian citizens. However, the plant is commonly infected by white pustule symptom of particular pathogen on it’s leaves. The pustule known as white blister, is common disease in I. reptans Poir. leaves in Indonesia. Even so, till time, there was no microscopic description of this pathogen ever provided in previous reports in Indonesia. This study aimed to provide the biological information on the morphological and microscopic characteristics of the certain pathogen. The result revealed that the microorganism was Albugo ipomeae-aquaticae Sawada with brief characteristics in the following result.